Analysis of Traffic Noise Levels on the Jalan Adi Sucipto, Kubu Raya Regency - Forbes, Hendy Hansen; Said, Said; Kadarini, S. Nurlaily (Fakultas Teknik Universitas Tanjungpura, 2025)
The 1.75% population growth in Kubu Raya Regency since 2020 has intensified transportation activities, leading to increased traffic noise along Adi Sucipto Road and negatively affecting community comfort and health. This study analyzes traffic noise levels, develops a predictive regression model using JASP, and proposes mitigation strategies. The research employed a quantitative method, with primary data collected through field observations on July 20